2013
DOI: 10.1186/1750-1326-8-16
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 induces Aβ42, tau, and neuronal pathology in the hippocampus of young targeted replacement apoE4 mice

Abstract: BackgroundRecent findings suggest that the pathological effects of apoE4, the most prevalent genetic risk factor for Alzheimer’s disease (AD), start many years before the onset of the disease and are already detectable at a young age. In the present study we investigated the extent to which such pathological and cognitive impairments also occur in young apoE4 mice.ResultsThis study revealed that the levels of the presynaptic glutamatergic vesicular transporter, VGlut, in the CA3, CA1, and DG hippocampal subfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
96
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 103 publications
(124 reference statements)
15
96
1
1
Order By: Relevance
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study revealed that the performance of the apoE4 mice in the object recognition and Morris water maze was impaired relative to that of the apoE3 mice and that it was also impaired in the contextual but not in the cued fear conditioning response.These findings are in accordance with previous results obtained utilizing a dry version of the Morris water maze and fear conditioning test results, which were obtained using young apoE4 mice [23,30]. They also extend previous studies that revealed that adult apoE4 mice are cognitively impaired [32,34,36,37,41,42,43,44] and suggest that, like in humans, the apoE4-driven cognitive impairments begin early in life [45,46].…”
Section: Discussionsupporting
confidence: 93%
“…These biochemical findings were in accordance with impaired performance of the apoE4 mice in a dry version of the Morris water maze [23]. …”
Section: Introductionsupporting
confidence: 66%
“…Cdk5 may be influenced by or interact with both pathways, and its activation triggers DNA damage, cell cycle activation and neurodegeneration [231] . Non-Aβ factors such as Tau and ApoE also contribute to AD pathology [232] . All these pathways can lead to synaptic dysfunction, neurodegeneration and AD.…”
Section: Non-aβ Hypothesismentioning
confidence: 99%
“…Note that the present line of apoE4-TR mice was crossed with C57Bl mice from Harlan, which lack the pre-synaptic protein synuclein (Specht and Schoepfer 2001). Preliminary findings utilizing apoE4 mice crossed with C57Bl mice, which have normal synuclein levels, suggest that phenotypes not directly related to the nerve terminal (e.g., apoE4-driven accumulation of Ab and hyperphosphorylated tau; Liraz et al 2013) are not affected by synuclein deficiency. The extent to which the apoE4-driven cholinergic impairments are accentuated by the lack of synuclein remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…However, since apoE4 also affects non-cholinergic synaptic parameters, e.g. reduction of the pre-synaptic glutamatergic transporter VgluT in hippocampus (Liraz et al 2013) or increase in VgluT transporter and disturbance of the glutamate-glutamine cycle in whole brain (Dumanis et al 2013), additional brain structure-specific mechanisms may play a role in mediating the synaptic pathological effects of apoE4.…”
Section: Discussionmentioning
confidence: 99%